"I Want, a Diocese Alive!" The First Decade of the Diocese of Lurín: 1996-2006 - Osorio Torres, Juan Alberto (2019)
At the end of the last century, the archdiocese of Lima gave birth by dismemberment to the triplets of the new dioceses of Lima: Carabayllo, Chosica and Lurín. This event, which was conceived and developed over more than four decades of a certain pastoral theological model (1954-1996), had in José Gurruchaga, founder of the Diocese of Lurín, the 'father bishop' who resumed with a seal original the structural bases of such a model.From the theology and anthropology of the diocese, different aspects of the implementation of the new diocese of Lurin are described and interpreted, noting in such a foundational phase, the features not only of a new pastoral theological model, which was dissociated from the model theological pastoral dominant. What is found and recorded is also how much it represents and means the installation of the diocese of South Lima during its first foundational decade for the Church of the future, that is, for the pastoral theological functioning of the same DL and the rest of the new dioceses and centenarians of the Catholic world.